Runoff Detected by Magnetic Resonance Angiography as an Indicator for Better Recanalization Outcomes in Below-the-Knee Chronic Total Occlusions in Diabetic Patients. (April 2015) - Zhu, Yue-Qi; Wang, Jue; Tan, Hua-Qiao; Lu, Hai-Tao; Liu, Fang; Cheng, Ying-Sheng; Wei, Li-Ming; Zhang, Pei-Lei; Zhao, Jun-Gong
Purpose: To compare the feasibility and efficacy of recanalizing below-the-knee (BTK) chronic total occlusions (CTOs) between patients with good or poor distal runoff based on magnetic resonance angiography (MRA) scans.Methods: Two hundred long-segment BTK CTOs in 171 limbs of 113 diabetic patients (58 men; mean age 69.8±1.9 years) were divided into good distal runoff (GDR: 119 lesions, 98 limbs) or poor distal runoff groups (PDR: 81 lesions, 73 limbs) based on baseline MRA findings. After angioplasty, modified thrombolysis in myocardial ischemia (mTIMI) grades and ankle-brachial index (ABI) were used to assess immediate outcomes. Regularly scheduled duplex or MRA imaging was performed in follow-up. The restenosis and limb salvage rates were compared.Results: The success rates were 93.3% and 87.7% in the GDR and PDR groups, respectively (p=0.21); subintimal angioplasty was more common in the PDR group (93.0% vs. 63.1%, p<0.01). Completion angiography indicated an mTIMI grade 3 blood flow in 71.2% lesions in the GDR patients and in 52.1% in the PDR (p=0.01) group. Improvement in the ABI was greater in the GDR limbs (p<0.001 vs. PDR). Mean imaging follow-up was 10.8±6.9 months in the GDR group and 11.1±6.6 months in the PDR group. Kaplan-Meier analysis showed a better restenosis-free rate in the GDR group (80.6% vs. 61.7%; p=0.02) at 12 months and for lesions with mTIMI grade 3 flow (p<0.01). At 24 months, Kaplan-Meier analysis revealed a better limb salvage rate in the GDR group (84.2% vs. 54.6%; p=0.02).Conclusion: Distal runoff detected using MRA could be a predictor for successful intraluminal recanalization, better distal tissue perfusion, improved long-term patency, and better limb salvage for patients with BTK CTOs.